(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: The COVID-19 pandemic is a major challenge for health care services including safe and effective surgery. This study aims to analyze gynecological surgery delivery during COVID-19 pandemic. Method: Data on gynecologic surgeries performed at Patan Hospital from 01 Jan to 31 Dec,2020 during pre-lockdown , lockdown and post-lockdown period of the COVID-19 pandemic were analyzed from medical record for surgical procedures, blood transfusion, ICU stay, length of hospital stay, mortality, COVID-19 PCR positive cases. Chi-square and Anova tests were used to compare between three periods, p value <0.05 was considered statistically significant. Ethical approval was obtained. Result: Out of 413 surgeries, 149(36.1%) were done during pre-lockdown, 116(28.1%) during lockdown and 148(35.8%) during post-lockdown period. Major surgery was 155(37.5%), minor 249(60.3%), minimally invasive 9(2.2%) and 61(14.8%) required blood transfusion. Mean hospital stay was 3.75±3.711 d, 15(3.63%) stayed in ICU following procedure and 1(0.2%) expired. Thirteen patients were suspected with COVID-19 infection 8 were PCR positive. Conclusion: There was decrease in major procedures during lockdown period.